Get Training or Wait? Long-Run Employment Effects of Training Programs for the Unemployed in West Germany - Aderonke Osikominu; Bernd Fitzenberger; Robert Völter (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
Long-term public sector sponsored training programs often show little or negative short-run employment effects and often it is not possible to assess whether positive long-run effects exist. Based on unique administrative data, this paper estimates the long-run differential employment effects of three different types of training programs in West Germany. We use inflows into unemployment for the years 1986/87 and 1993/94 and apply local linear matching based on the estimated propensity score to estimate the effects of training programs starting during 1 to 2, 3 to 4, and 5 to 8 quarters of unemployment. The results show a negative lock-in effect for the period right after the beginning of the program and significantly positive treatment effects on employment rates in the medium- and long-run. The differential effects of the three programs compared to one another are mainly driven by differences in the length of the lock-in periods.
More recent version: http://hdl.handle.net/10419/24650
Keywords: C14; J68; H43; 330; multiple treatments; training programs; employment effects; local linear matching; administrative data; active labor market programs; Arbeitsmarktpolitik; Weiterbildung; Wirtschaftspolitische Wirkungsanalyse; Arbeitslosigkeit; Berufliche Integration; Schätzung; Deutschland